The comparison of the repair bond strength of the composite resin to direct and indirect composite restorations with different surface preparations - Hasibe Sevilay Bahadir; Selin Polatoğlu; Duygu Tuncer; Çiğdem Çelik (Tabriz University of Medical Sciences, 2023)
Background. Indirect restorations have been employed in restorative dentistry to solve some of the drawbacks of direct restorations. The aim of this study was to evaluate the effect of different modes of a universal adhesive resin on the repair capacity of two indirect resin composites and a direct resin composite. Methods. Indirect composite resins (Ceramage and Gradia Plus) and a direct composite resin (Filtek Z250) were prepared in a plastic mold with a height and diameter of 2-mm and 6-mm, respectively. Composite blocks were thermocycled (5000 cycles, 5°C-55°C). Then, according to their surface treatments, composite blocks were categorized into six-groups: Group 1: ER (etch&rinse), Group 2: SE (self-etch), Group 3: Bur+ER (bur+etch&rinse), Group 4: Bur+SE (bur+self-etch), Group 5: Bur+Silane+ER (bur+silane+etch&rinse), Group 6: Bur+Silane+SE (bur+silane+self-etch), respectively. After surface treatments and adhesive application for bonding with a direct resin composite, all groups were then thermocycled before performing shear-bond-strength-test. Failure modes were evaluated using a stereomicroscope. Data were analyzed by two-way-ANOVA and Bonferroni-test (P<0.05). Results. The highest bond-strength values were obtained for Bur+Silane+SE groups, while the lowest values were obtained for the Bur+Silane+ER groups for all materials. Statistically significant differences were observed between the Bur+Silane+ER group and ER, Bur+ER and Bur+Silane+SE groups in Gradia Plus (P<0.05). Conclusion. The self-etch-mode of the universal-adhesive and silane applications led to the increase in the repair-strength of the adhesive in the Filtek Z250 and Ceramage. The self-etch-mode of the universal-adhesive might be used to reduce adhesive-application-steps in the clinical repair procedures.